2021
DOI: 10.4103/ija.ija_423_20
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesic efficacy of the pulmonary recruitment manoeuvre compared to intraperitoneal hydrocortisone in laparoscopic gynaecological surgeries

Abstract: Background and Aims: Laparoscopic surgeries are becoming attractive because of early recovery. Adequate postoperative pain relief may be a major concern. Several methods have been used to relieve laparoscopic postoperative pain. Methodology: This prospective, randomised, controlled study was conducted during the period between February and June 2019. Patients were assigned into three groups. Patients in the hydrocortisone group received intraperitoneal 100mg hydrocortis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Sultan et al reported that the preoperative administration of 0.1 mg/kg single-dose IV dexamethasone could enhance the quality of patient recovery and improve pain control after laparoscopic cholecystectomy, compared to lignocaine (23). Additionally, Elsakka et al studied the effect of different corticosteroids on POP and proved that the administration of IP dexamethasone and hydrocortisone could reduce abdominal pain and shoulder pain in patients and consequently reduce the need for the administration of analgesics after laparoscopic chole-cystectomy, without causing any significant side effect to patients (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Sultan et al reported that the preoperative administration of 0.1 mg/kg single-dose IV dexamethasone could enhance the quality of patient recovery and improve pain control after laparoscopic cholecystectomy, compared to lignocaine (23). Additionally, Elsakka et al studied the effect of different corticosteroids on POP and proved that the administration of IP dexamethasone and hydrocortisone could reduce abdominal pain and shoulder pain in patients and consequently reduce the need for the administration of analgesics after laparoscopic chole-cystectomy, without causing any significant side effect to patients (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] Reduction of physical irritation can be achieved by using gas warming,[ 13 ] low pneumoperitoneal pressures, low gas insufflation rates,[ 14 ] or even use of gasless laparoscopy. [ 15 ] Moreover, other interventions dealt with the pain signal itself by suppressing its initiation using anti-inflammatory medications,[ 16 ] blocking its transmission by applying a local anaesthetic solution to the diaphragmatic surface at the end or beginning of surgery,[ 17 18 19 ] intraperitoneal instillation of additional dexmedetomidine or clonidine along with bupivacaine,[ 20 ] use of intraperitoneal hydrocortisone[ 21 ] or use of intrathecal clonidine. [ 22 ] The use of low-pressure laparoscopy provides a decrease in both physical and chemical irritation inputs and this explains the suggestion by Donatsky et al .…”
Section: Discussionmentioning
confidence: 99%